(untitled) (Research, Society and Development, 2022)
The various transformations that have taken place in society in recent decades have led to reforms in Education. The most recent and significant change in Brazilian Education was the reform of Secondary Education under Law 13,415/2017, forcing federation entities to rethink their curricula. Therefore, in this article we discuss the possibilities that the Capixaba Curriculum offers to Critical Mathematics Education in the context of the New High School. In this sense, we go through the legal frameworks that support the High School Reform and we will analyze the Capixaba Curriculum supported by Skovsmose’s (2001) studies on Critical Mathematics Education. The work methodology acquires a qualitative character with document analysis. In this way, it was possible to observe that although the High School Reform has a strong appeal to the construction of the neoliberal subject, it is possible to adopt a critical stance from the Capixaba Curriculum, which presents alternatives in its text and in its integrating themes as a field of discussion.